A Combined Fuzzy AHP-Hybrid TOPSIS Methodology to Determine Smelter Project Selection - Dimas Rahfaditya Pradana; Utomo Sarjono Putro (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2025)
This study aims to give recommendations on smelter project selection based on three alternatives: the Alumina Processing Plant, the Pig Iron Processing Plant, and MHP HPAL Nickel Plant by using a hybrid decision-making method Fuzzy AHP and Hybrid TOPSIS. The method integrates both qualitative expert judgments and quantitative data to ensure objectivity of analysis. Expert input was collected through structured interviews and questionnaires, capturing a diverse range of perspectives from technical, operational, and management roles. The Pairwise Comparison questionnaire data are analyzed using Fuzzy AHP to calculate the weights of these criteria, addressing the ambiguity in human judgment through triangular fuzzy numbers. These fuzzy weights were then combined with quantitative performance data for each project using Hybrid TOPSIS, ensuring the final ranking accounted for both qualitative and quantitative factors. The results showed that the Alumina Project achieved the highest closeness coefficient of 0.6, making it the most feasible and strategic project for immediate development. The Pig Iron Project ranked second, reflecting its stable production capacity and technical maturity, though it faces challenges from environmental impacts and a limited domestic market for pig iron. The MHP Nickel Project ranked third due to its complex environmental footprint, high capital intensity, and current market volatility, despite its relevance to the EV battery sector.